Introduction and uptake of electronic growth charts in southern New Zealand. (13th September 2018) - Dainty, Gloria J; Reith, David M; Taylor, Barry J
Abstract : Aim: The introduction of an electronic system for recording and displaying growth measurements replaces multiple paper growth charts and theoretically improves the availability and consistency of information to support clinical decision‐making. Introducing this in a single New Zealand District Health Board provided the opportunity to evaluate usage in hospital settings and determine the uptake of growth recording in a defined population. Methods: All records between 2010 and 2015 in the Southern District Health Board (SDHB) anthropometry database were downloaded and examined in a retrospective cohort analysis. Records were extracted after matching to demographic and clinical setting data from the hospital patient management system. Results: Analysis included 30 670 data entry points, representing 8551 children. Data entry increased over time to a maximum of 8407 observations in 2015. By the fifth year of use, up to 67% of available clinical encounters had anthropometry recorded in the outpatient department. Rates were lower in the inpatient setting, where only up to 18.4% had anthropometry recorded. The errors identified were low (0.2% of all data). Weight was the most commonly recorded measurement (98.2% of anthropometry entries, 35.1% of available clinical presentations). Height was available for 82.6% of entries and 29.5% of presentations. A body mass index z ‐score was available for 81.5% of entries and 29.1% of presentations. A head circumference was available for 50.2% of children <2 years age who had anthropometry recorded. Conclusions: The introduction of an electronic anthropometry database has been successful with increasing rates of use over time, especially in outpatient clinics. Further focus to improve inpatient recording of height and weight is needed.